PEMANFAATAN APLIKASI KOMUNITAS BISA MENULIS (KBM APP) DALAM UPAYA MENINGKATKAN KEMAMPUAN MENULIS CERITA PENDEK DI KELAS V - Muhammad Luthfi Setyawan Anshory; Kurniawati; Setyaningsih Rachmania (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Writing is one of the language skills that students need to master, including writing short stories. However, students often face challenges such as lack of motivation and interest, and consider writing as a boring task. KBM App is an application that can be used to write and publish works, so it can help improve students' writing skills. This study aims to analyze the effect of utilizing KBM App in improving the short story writing skills of fifth grade students. The method used is a quasi-experimental method with a pre-test and post-test design on fifth grade students. The results of the study showed a significant increase in students' writing skills after using KBM App. T-test analysis showed that there was a positive effect on improving short story writing skills. The results of the N-Gain test in the experimental class showed a "quite effective" category with a value of 0.6504 (65.04%), while the control class only reached 0.3583 (35.83%) which was included in the "ineffective" category. Thus, KBM App can be a fairly effective alternative in improving short story writing skills in elementary schools.